The Influence Of Opporunity Recognition, Self-Efficacy Dan Entrepreneurial Attitude To Entrepreneurial Intention - Marcello Marcello; Oey Hannes Widjaja (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to analyze the research variables of Opportunity Recognition, Self-efficacy, and Entrepreneurial Attitude towards Entrepreneurial Intention of Generation Z in Building a Business in Jakarta City. The background of this study is the increasing environmental problems such as the amount of waste that often increases in the Jakarta City area. Generation Z is a generation that was born and grew up in a more advanced digital era and is aware of the issues that occur. Generation Z has great potential in creating a business that is not only to achieve profit, but also for the sustainability of the business. The sample used in this study was 160 respondents who were generation z who wanted to build a business in Jakarta City and who had the intention of preserving the environment to reduce the amount of excessive waste and purposive and snowball sampling techniques. The data used in this study were collected through questionnaires distributed digitally using Google Forms and data analysis methods using SmartPLS 4.0 software. In analyzing the data, it can be concluded that Opportunity Recognition has no effect on Entrepreneurial Intention, Self-Efficacy has a significant effect on Entrepreneurial Intention, and Entrepreneurial Attitude has a significant effect on Entrepreneurial Intention. This study provides theoretical suggestions for further researchers such as adding variables not discussed in this study and collecting more samples to be able to analyze further.